THE ADEQUACY OF THE EVIDENCE IN THE CASE OF EVIL CONSPIRACY OF NARCOTICS CRIMINAL REVIEWED BY EVIDENTIARY THEORY - Veronika Sihotang; Widati Wulandari; Erika Magdalena Chandra (Faculty of Law, Universitas Sebelas Maret, 2020)
Narcotics crime has been considered as a global crime and big issues in attempt to prevent and also by eradicate it. It's not only happens in Indonesia but also for other countries. Narcotics crime in most cases involves more than one person, who cooperates in narcotics crime. One of the criminal act involve more than one person is a conspiracy of narcotics crime. The involvement in the conspiracy is shown by two or more people agree to do narcotics crime. Admissible evidence in conspiracy of narcotics crime becomes the important issue in some of conspiracy's cases. This study used the method of judicial normative approach to review and examine the primary data such as judge's Decision and the secondary data such as related law. The purpose of this study is to know and understand whether the absence of evidence to support the defendant's denial can be the basis to proof personal's guilt and to understand how the quality of the witness testimony can be the basis of criminal conviction.